Tingkat Kepatuhan Penggunaan Obat Symbicort 160 Microgram pada Pasien Asma di Instalasi Farmasi Rawat Jalan RS Dr Hafiz Cianjur: Compliance Level of Symbicort 160 Microgram Medication in Asthma Outpatient at the Pharmacy Installation of Dr. Hafiz Hospital, Cianjur - Muchammad Nagib Idris; Oci Etri Nursanty; Julia Totong (Jurnal Ilmiah Farmasi Indonesia (JIFIN), 2024)
Compliance with regular use of asthma control drugs is still low, which can increase morbidity and mortality rates. One factor that influences compliance is knowledge. Asthma is a chronic inflammatory disorder of the airways that involves many cells and elements. This research aims to determine the level of compliance with the use of the drug Symbicort 160 Micrograms in asthma patients at the outpatient pharmacy installation at Dokter Hafiz Cianjur Hospital. This research uses descriptive research methods with a quantitative approach. Research sampling was carried out using a total sampling technique using the time-limited sampling method, namely all patients suffering from asthma who met the inclusion criteria of the study and entered the specified research time period, namely 1 May-31 July 2023. The number of respondents was 52 people; 43 people were selected. because there are several factors, namely age. The instrument used in this research was the Morisky Medication Adherence Scale (MMAS) questionnaire. Of the 43 respondents, 22 (51.16%) had a high level of compliance, 20 (46.51%) had a medium level of compliance, and 1 (2.33%) had a low level of compliance. The compliance level of most patients using Symbicort 160 Microgram medication is at a high level, namely 22 respondents (51.16%), indicating a good understanding and commitment to asthma treatment. This study concludes that the level of compliance with the use of Symbicort 160 Microgram medication in asthma patients shows that the level of compliance of most patients using Symbicort 160 Microgram medication is at a high level, namely 22 respondents (51.16%), indicating a good understanding and commitment to asthma treatment.